Pap smear and cervical cancer in transgender men: integrative review (Research, Society and Development, 2021)
Introduction: Pap smear is the main screening method for cervical cancer, which can affect transgender men who have this organ. Objective: To highlight the importance of cytopathological examination in the fight against cervical cancer in transgender men. Methodology: It is an integrative literature review of a descriptive nature and qualitative approach, carried out on the SciELO, PUBMED, MEDLINE, LILACS, VHL and Science Direct databases, using the descriptors "Transgender Persons", "Uterine Cervical Neoplasms" and "Papanicolaou Test". Articles from 2015 to 2020 that address Pap smear and cervical cancer or cancer precursor lesions in transgender men were included. The analysis took place through critical reading and thematic categorization. Results and discussion: Eight articles were found that originated three categories: Screening for cervical cancer in transgender men, history related to the Pap smear and perceptions about screening for cervical cancer. Thus, it was found that transgender men do not screen for cervical cancer like cisgender women and face unique challenges in the Pap smear, relevant to each reality, leading them to seek alternatives that minimize their discomfort. Conclusion: The data reveal the importance of the Pap smear in the screening of cervical cancer in transgender men, since compared to alternative means sought, it is the most reliable today. Still, they reinforce the need for knowledge for individualized screening in this audience.